Identification of New Sources of Resistance to Wheat Stem Rust in Aegilops spp. in the Tertiary Genepool of Wheat - Olivera, Pablo D.; Rouse, Matthew N.; Jin, Yue (Frontiers in Plant Science, 2018)
Recent stem rust epidemics in eastern Africa and elsewhere demonstrated that wheat stem rust is a re-emerging disease posing a threat to wheat production worldwide. The cultivated wheat gene pool has a narrow genetic base for resistance to virulent races, such as races in the Ug99 race group. Wild relatives of wheat are a tractable source of stem rust resistance genes. Aegilops species in the tertiary genepool have not been exploited to any great extent as a source of stem rust resistance, however. We evaluated 1,422 accessions of Aegilops spp. for resistance to three highly virulent races (TTKSK, TRTTF and TTTTF) of Puccinia graminis f. sp. tritici. Species studied include Ae. biuncialis, Ae. caudata, Ae. comosa, Ae. cylindrica, Ae. geniculata, Ae. neglecta, Ae. peregrina, Ae. triuncialis, and Ae. umbellulata that do not share common genomes with cultivated wheat. High frequencies of resistance were observed as 977 (68.8%), 927 (65.2%), and 850 (59.8%) accessions exhibited low infection types to races TTKSK, TTTTF, and TRTTF, respectively. Association analyses showed strong association for resistance to different races in several Aegilops spp., indicating that for a given species, the resistance genes effective against multiple races. Inheritance studies in selected accessions showed resistance to race TTKSK is simply inherited.